PENGARUH PERLUASAN MEREK TERHADAP PENINGKATAN VOLUME PENJUALAN KENDARAAN BERMOTOR PADA PT. SINAR GALESONG PRATAMA MAKASSAR - Muhammad Saleh (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2009)
From result of calculation of correlation coefficient of among expense of brand extension with the volume of sale of motor vehicle of wheel two at PT. Sinar Galesong Pratama Makassar is hence obtained by correlation coefficient of equal to 0,94 or 94 % hence this matter is explainable that influence of among expense of brand extension with the volume of sale kendaraan enough is strong. Than result test by parsial is obtained by conclusion that each;every variable independent (x) have an effect on to change assess the variable dependen (y). Assess the coefficient determinasi (r²) that is 0,88 this show the level of influence of all variable independent (x) is equal to 88 % while rest that is equal to 12 % influenced by variable of besides the variable (x). Thereby there are relation